PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN TERHADAP MOTIVASI PENGURUS ORGANISASI KEMAHASISWAAN (Pada Unit Kreativitas Mahasiswa Jam’iyyatul Qurro’ Wal Huffadz UNISMA) - Kholidatuz Ziyah; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to examine and analyze the influence of leadership style and commitment to the motivation of the management of student organizations in the student creativity unit jam'iyyatul qurro 'wal huffadz UNISMA. This research is Explanatory Research. This research was conducted at the management of the student creativity unit jam'iyyatul qurro 'wal huffadz UNISMA. The population and sample in this study were 63 people. Data collection was done by distributing questionnaires. Data analysis in this study uses SPSS version 20. The data collection technique used is to use the census method and the testing technique used in this study using the Instrument Test, Normality Test, Multiple Linear Regression Analysis, Classical Assumptions, and Hypothesis Tests. Based on the results of this study, it can be concluded that partially the Leadership Style does not have an important effect on the Motivation of Student Organizational Managers and the Commitment variable has an important effect on the Motivation of Student Organizations and simultaneously the Leadership Style and Commitment variables significantly influence Motivation. This means that the independent variable is feasible to explain the independent variables analyzed.Keywords: Leadership Style and Commitment to Motivation of the management of Student Organizations